The eyes of power : art and early Tokugawa authority - Gerhart, Karen M., 1949- (University of Hawai'i Press, 1999)
In the first half of the seventeenth century both those who commissioned and those who viewed art in Japan were primarily the elite -- the shogun, the court, high-ranking daimyo, government officials, and certain wealthy merchants. Much of the artistic energy engaged by the political center during the early Tokugawa was directed at the creation of monumental structures decorated with symbolic and complex images, mainly of Chinese origin, initiated or approved by the shogunate to legitimate its own power and to give its rule an aura of cultured sophistication.